THE ROLE OF “PADARKUSH” IN UZBEK DRAMATURGY AND THEATRE - Kuchkarova Marhabo Khudoyberganovna (International Journal of Literature and Language Studies, 2026)
This article examines the history of the creation and publication of the drama “Padarkush,” which was first written and staged in the literature of the peoples of Central Asia by Mahmud Khoja Behbudiy. It also discusses the real-life and artistic foundations that formed the basis of the drama, as well as the analyses and interpretations offered by Uzbek and foreign scholars of Uzbek studies.